TOWARDS CONFIGURING INFORMATION SYSTEMS FOR MANAGING COLLABORATIVE PROJECTS (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
IInformation Systems have an eminent role for successful management of large projects which involve multibodies. These bodies have to work together and also share important information for successful scheduling and development of the project. So, management of information systems is very necessary to provide centralized documents in order to satisfy information needs of different persons having different interests and roles for the project. So, a need arises for a platform which is able to develop the above mentioned information systems. This paper discusses the functional requirements for these information systems. A methodology has also been configured for developing information systems which serve the development of collaborative projects.